Gastrointestinal parasites of different avian species in Ilorin, North Central Nigeria - Fadunsin, Shola David Ola; Ganiyu, Isau Aremu; Rabiu, Musa; Hussain, Karimat; Sanda, Idiat Modupe; Musa, Salamat Ayinke; Uwabujo, Patricia Isioma; Furo, Nathan Adamu (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The current study aimed to determine the prevalence, infection burden, and risk factors associated with the occurrence of gastrointestinal (GI) parasites in different avian species in Ilorin, Nigeria. Materials and Methods: This study was conducted in Ilorin, involving 597 fecal samples and GI tracts from a variety of sold and slaughtered avian species. The study was conducted between September 2017 and February 2018. Fecal samples were examined using floatation technique, while the GI tracts were examined for gross helminths and its content were subjected to the direct wet mount examination. Data were analyzed using percentages (descriptive) and the Chi-square (χ2) test (inferential). p < 0.05 was considered significant for all analysis. Results: Ten GI parasites were detected with Eimeria species (32.83%), Ascaridia galli (30.15%) and Heterakis gallinarum (24.79%) as the most prevalent ones. Multiple parasites co-infection was recorded in all the avian species: broilers (77.78%), layers (33.33%), cockerels (45.16%), indigenous chickens (17.91%), ducks (69.70%), pigeons (94.12%), turkeys (47.83%), and guinea fowls (77.36%). Pigeons (100.00%) and turkeys (95.65%) were the most infected avian species. Age, sex, and avian types were significantly (p < 0.05) associated with the occurrence of GI parasites infection. Conclusion: This study gives a reflection of the GI parasites fauna of avian species in Nigeria. The GI parasites are endemic among different avian species in Ilorin, North Central Nigeria. Knowledge on the epidemiology of these parasites is important in instituting a good preventive and control measures against GI parasites, so as to have maximum production and reproduction effects in the poultry industry. J. Adv. Vet. Anim. Res., 6(1): 108-116, March 2019